2015
DOI: 10.3390/ma8041413
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Pellets from Different Sources

Abstract: The rise in pellet consumption has resulted in a wider variety of materials for pellet manufacture. Thus, pellet industry has started looking for alternative products, such as wastes from agricultural activities, forestry and related industries, along with the combination thereof, obtaining a broad range of these products. In addition, the entry into force of EN ISO 17225 standard makes wood pellet market (among other types) possible for industry and household purposes. Therefore, wastes that are suitable for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(98 citation statements)
references
References 24 publications
6
88
0
4
Order By: Relevance
“…The trials T 3 and T 5 have high DU than T 13 and T 1 due to difference in their BD. These results had been supported by Miranda et al (2015).…”
Section: Fig 4 Effect Of Relationship On Rdf Properties (A) E and Bsupporting
confidence: 59%
“…The trials T 3 and T 5 have high DU than T 13 and T 1 due to difference in their BD. These results had been supported by Miranda et al (2015).…”
Section: Fig 4 Effect Of Relationship On Rdf Properties (A) E and Bsupporting
confidence: 59%
“…Although ENplus is the benchmark for wood pellets, in recent years standards have been emerging for straw and grass fuel pellets (Carroll & Finnan, 2012;Miranda et al, 2015). As markets develop, greater value will be placed on quality, and meeting these standards will require management of quality throughout the supply chain from grower through to end user.…”
Section: Agronomic Practices In Miscanthus Quality Improvementmentioning
confidence: 99%
“…al. [16] studied the influence of the moisture content and bulk density on the durability of pellets obtained from 10 types of biomass: pyrenean oak (PO), pyrenean sylvestris (PS), cork powder (CP), pine sawdust (SW), vine shoots (VS), olive branches (OB), barley straw (BS), wheat straw (WS), olive pomace (OP) and grape pomace (GP). The highest durability was obtained for the moisture contents between 6.5-10.8 %.…”
Section: Moisture Contentmentioning
confidence: 99%
“…al. [16] reported that most pellets, with densities of 582-700 kg·m -3 had high durability. The highest densities were obtained for agroindustrial wastes (OP and GP) showing the lowest durability.…”
Section: Fig 2 Relationships Between Moisture and Durability [16]mentioning
confidence: 99%